Amino acids as latent curing agents and their application in fully bio-based epoxy resins. Issue 17 (10th August 2021) - Yu, Zhen; Ma, Songqi; Tang, Zhaobin; Liu, Yanlin; Xu, Xiwei; Li, Qiong; Zhang, Kewei; Wang, Binbo; Wang, Sheng; Zhu, Jin
Abstract : Amino acids were exploited as a new type of latent curing agent and utilized to achieve bio-based one-component epoxy resins. Abstract : Latent curing agents are significantly important to develop one-component epoxy resins. However, the reported latent curing agents are from unsustainable fossil resources. Herein, a new type of latent curing agent—amino acids—was developed from bioresources. Amino acids can be naturally occurring and can also be synthesized from bio-based compounds. The latent curing feature and mechanism were revealed through investigation of curing kinetics and small-molecule model curing reaction. A bio-based amino acid containing amide bond (PDA-MAH) was synthesized from 1, 5-pentanediamine and maleic anhydride, and used together with a bio-based epoxy monomer from itaconic acid (EIA) to achieve a fully bio-based one-component epoxy system. The obtained epoxy network exhibited significantly enhanced glass transition temperature, tensile strength and Young's modulus compared with the control amino acid/EIA system due to the hydrogen bonding from the amide bonds. In addition, the epoxy network exhibited excellent degradability under alkaline conditions.